The Relevance of Victimization Experiences for Predicting the Development of Threat Symptoms During Adolescence and Early Adulthood - Wojciechowski, Thomas W. (Journal of interpersonal violence, 2021)
The “threat” portion of the threat/control override symptom constellation is characterized by the belief by an individual that others seek to do them harm. There has yet to be an examination of the link between perceived threat symptomatology and the experience of victimization, despite the fact that both constructs are linked to the perpetration of violent behavior. Furthermore, there has yet to be research which examines the heterogeneity in developmental patterns of threat symptomatology. The present research utilized the Pathways to Desistance data to model the developmental heterogeneity in perceived threat symptomatology across adolescence and early adulthood using group-based trajectory modeling. A series of multinomial logistic regression models were then estimated to examine the relevance of victimization experiences for predicting trajectory group assignment. A five-group model of development during adolescence and early adulthood best fit the threat symptom data. Victimization experienced prior to age 16 predicted assignment to all groups in the model characterized by presentation of threat symptoms at some point during the study. Victimization experienced between ages 16 and 23 predicted assignment to the High Chronic group and marginally predicted assignment to the Accelerating group. These results indicate that victimization does indeed predict the presentation of perceived threat symptomatology. This indicates that presentation of threat symptoms may be indicative of a history of victimization. Proper screening of those presenting threat symptoms may help to better orient treatment plans for modalities centered on victimization experiences. Future research should investigate the possibility that threat symptoms mediate the relationship between victimization and violent behavior.